Investigation of the Presence of Biofilms in Chronic Suppurative Otitis Media, Nonsuppurative Otitis Media, and Chronic Otitis Media with Cholesteatoma by Scanning Electron Microscopy - Ercan Kaya; Ilknur Dag; Armagan Incesulu; Melek Kezban Gurbuz; Mustafa Acar; Leman Birdane (The Scientific World Journal)
Objective. Biofilms have been shown to play a major role in the pathogenesis of otolaryngologic infections. However, very limited studies have been undertaken to demonstrate the presence of biofilms in tissues from patients with chronic otitis media (COM) with or without cholesteatoma. Our objective is to study the presence of biofilms in humans with chronic suppurative and nonsuppurative otitis media and cholesteatoma. Study Design. In all, 102 tissue specimens (middle ear, mastoid tissue, and ossicle samples) were collected during surgery from 34 patients. Methods. The samples were processed for the investigation of biofilms by scanning electron microscopy (SEM). Results. Our research supports the hypothesis in which biofilms are involved in chronic suppurative otitis media, cholesteatoma, and, to a lesser degree, chronic nonsuppurative otitis media. There were higher rates in hypertrophic and granulated tissue samples than in normal mucosa. In addition, the presence of biofilms was significantly higher in the middle ear mucosa compared with the mastoid and ossicle samples. Conclusion. In the clinic, the careful use of topical or systemic antimicrobials is essential, and, during surgery, hypertrophic tissue must be carefully removed from normal tissue.